Cognitive performance of Neuromyelitis Optica patients: comparison with Multiple Sclerosis - Vanotti, Sandra Inés (2013)
Objective The aim of the present research was to investigate cognitive pattern of patients with NMO and compare it with MS patients? performance. Methods Fourteen NMO patients, 14 RRMS patients, and 14 healthy controls participated. Neuropsychological functions were evaluated with the Brief Repeatable Neuropsychological Battery for MS; Symbol Digit Modalities Test; Digit Span; and Semantic fluency. Results Fifty seven percent of NMO patients and 42.85% of MS patients had abnormal performance in at least two cognitive tests. The NMO group showed abnormal performance in verbal fluency, verbal and visual memory, with a greater attention deficits. NMO pacients outperformed heathy control in PASAT-2 seconds. However, no difference was found between NMO and RRMS patients. Conclusions The NMO group showed more dysfunction in attention and verbal fluency than in verbal and visual memory. When compared with the MS patients, a similar dysfunction pattern was found.